THE INFLUENCE OF HEDONIC PRODUCT, SELF-EXPRESSIVE BRAND, AND SATISFACTION ON BRAND LOVE AND BRAND LOYALTY: STUDY OF STARBUCKS’ CONSUMERS IN MALANG - Ramadhina, Farah Astri (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this study is to examine the effect of hedonic product, self-expressive brand, and satisfaction on brand love and brand loyalty of Starbucks from the perspective of consumers in Malang. The sample in this study was consumers of Starbucks in Malang. The sampling technique was convenience sampling with 133 respondents. This study used Partial Linear Square (PLS) analysis technique to analyze the data.The result of this study shows that hedonic product, self-expressive brand, and satifaction have significant effect on brand love. Meanwhile, self-expressive brand has a significant effect on brand loyalty. Moreover, brand love has significant effect on brand loyalty, while hedonic product and satisfaction have no significant effect on brand loyalty. In addition, brand love is indirectly enhancing the influence of hedonic product, self-expressive brand, and satisfaction to increase the level of brand loyalty. Thus, this study is useful for marketers to profoundly understand the importance of brand love in consumer-brand relationship.Keywords: Hedonic Product, Self-Expressive Brand, Satisfaction, Brand love, Brand Loyalty